BOOKS ONLINE BOOKING APPLICATION USING PHP AND MYSQL PROGRAMMING LANGUAGE - Hendro Siswanto; Fitri Syafrina, SKom, MMSI (Jurnal Sistem Informasi, 2009)
This will be discussed in writing this time, is about the application ordering books online to enable customers to buy books, not must come to the bookstore tangible and not so hard to find booksn the customer wants. The main target users of this application is the consumers are very hobbies are reading books. Created by none other than the Internet as a tool in terms of human helper solving problems, especially the complicated and numerous and kind. Because of the Internet, will be more effective human performance, one of them in terms of information systems services for the purchase of books is more accurate, fast and precise.